2000
DOI: 10.4049/jimmunol.164.2.805
|View full text |Cite
|
Sign up to set email alerts
|

Human Cytomegalovirus Gene Products US3 and US6 Down-Regulate Trophoblast Class I MHC Molecules

Abstract: The epidemiological correlation between human CMV (HCMV) infection and spontaneous fetal loss has been suggested, but the underlying mechanism is not well understood. Fetal cytotrophoblasts, which are in direct contact with the maternal immune system in the uterus during pregnancy, do not express HLA-A and HLA-B, but express the nonclassical class I HLA-G and HLA-C. It has been shown that both HLA-G and HLA-C are capable of inhibiting NK-mediated cell lysis. In our present study, using human trophoblast cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(77 citation statements)
references
References 40 publications
(36 reference statements)
3
74
0
Order By: Relevance
“…Interestingly, large numbers of NK cells are present within the maternal decidua close to trophoblast cells, and they express HLA-G-specific inhibitory receptors, including LIR-1 [34]. The capacity of HCMV to infect the trophoblast and to down-modulate HLA-G expression may render infected cells susceptible to recognition by NK cells [35,36]. However, in this context, expression of UL18 could provide an important inhibitory signal to NK cells.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, large numbers of NK cells are present within the maternal decidua close to trophoblast cells, and they express HLA-G-specific inhibitory receptors, including LIR-1 [34]. The capacity of HCMV to infect the trophoblast and to down-modulate HLA-G expression may render infected cells susceptible to recognition by NK cells [35,36]. However, in this context, expression of UL18 could provide an important inhibitory signal to NK cells.…”
Section: Discussionmentioning
confidence: 99%
“…Only few maternal CTLs are found at this site, and during HCMV infection T cell recognition of infected trophoblast cells will largely be prohibited due to absence or reduction of surface expression of Ag-presenting MHC class I molecules: HLA-A and -B molecules are lacking in these cells, and surface expression of HLA-G is reduced by US2 (this study), US3 (53), and US6 (54). In addition, HLA-C can be down-regulated by US3, US6 (53), and US11 (Ref. 55 and our own unpublished results).…”
Section: Discussionmentioning
confidence: 99%
“…It was previously shown that HCMV evasins differentially modulate detectable levels of MHC I molecules encoded by different loci (25,26,44,45). Products of the HLA-C and HLA-E loci were described to be resistant to US2 and US11 (26) but susceptible to US3 and US6 (45).…”
Section: Discussionmentioning
confidence: 99%